PERAN KEPEMIMPINAN KEPALA SEKOLAH MEMODERASI PENGARUH MOTIVASI DAN KOMPETENSI TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN PATI KABUPATEN PATI - 11.52.02.0100, Yayan Surian Syah (Jurnal Mahasiswa Pasca Sarjana, 2013)
This aims of this study is to examine the effect of jobâs motivation, teacherâs competence and the leadershipâs of Headmaster on teacherâs performance of Senior High School Teachers in Pati District. The Specific objective of this study is to examine the role of the Headmaster to moderates the influence of jobâs motivation and teacherâs competence on teacherâs performance. The benefit of this study is to describe and extend previous study of the role of the Headmaster to moderate the influence of jobâs motivation and teacherâs competence on teacherâs performance.This study used a sample of state junior high school teachers in Pati District. They are 90 teachers from 274 teachers. Sampling in this study is a nonprobability sampling with purposive sampling method, by taking data from teachers who meet the specific criteria of the overall population.Based on the results of the study can be summarized as follows: jobâs motivation to work had no effect on teacherâs performance, teacherâs competence had a significant and positive effect on teacher;s performance, the principals leadership does not influence on the performance of teachers, the principals leadership does not moderate the effect of jobâs motivation on teacherâs performance, the leadership of the headmaster strengthen the influences of teachers competence on teacherâs performance. Keywords: motivation, competence of teachers, school leadership and teacherâs performance